Environmental Insurance: Legal Protection and Certainty Mechanism in Recovery of Forest Damage Due to Land Burning - Verdinan, Verdinan; Adi Mansar; faisal (Faculty of Law, Universitas Pekalongan, 2024)
Environmental law enforcement against corporations that commit destruction is constrained by the execution of court decisions to carry out rehabilitation or compensation, where business actors do not intend to implement the decision. Therefore, environmental insurance can be a solution to cover compensation for environmental damage to realize legal certainty. The research conducted is normative juridical or research that analyzes written law, jurisprudence, and norms that live in society. The descriptive-analytical approach aims to take systematic, factual, and accurate data on a problem based on applicable laws and legal norms. The results of this study show that the legal basis for environmental insurance is regulated in Articles 42 and 43 of Law Number 32 of 2009 concerning Environmental Protection and Management jo Government Regulation Number 22 of 2021 concerning the Implementation of Environmental Protection and Management. The implementation of environmental insurance is constrained by insolvency problems by corporations who are required to make a recovery due to environmental damage but are not willing to pay compensation costs. Environmental insurance is a preventive and anticipatory effort as a guarantee to repair and restore the environment damaged by activities or businesses, especially plantations, as well as providing certainty in the enforcement of environmental laws following sustainable development goals.